ANALISIS DAN DESAIN WEBSITE MONITORING KONSULTASI BIMBINGAN KARTU RENCANA STUDI (KRS) (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2017)
Informatics Engineering, University of Palangka Raya still use some old methods (manual) on KRS. Therefore, a system to facilitate students, teachers, and administrators to input the value is needed. It can also save time and make it easier student counseling KRS with an academic supervisor. The research design was consists of two phases, namely, (1) collecting and analyzing data was done by library research and observation, (2) applied the waterfall method that has been modified with the stages, namely systems analysis to determine access rights with the facilities, UML and ERD were created, the system design to perform database design, navigation structure, interfaces, and (3) the results of the study are database blueprint, blueprint site map and blueprint website. The analyze and website design of KRS counseling monitor at Informatics Engineering, University of Palangka Raya generally will be made with three user, such as an administrator to manage information, lecturers to access the system to check the value and checking students who already consulting or not, and to access the value of IPS, IPK, and SKS that have been collected.